2017
DOI: 10.1080/15384101.2017.1338988
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CDK-mediated Smad3 phosphorylation reduces the Pin1-Smad3 interaction and aggressiveness of triple negative breast cancer cells

Abstract: Triple negative breast cancer (TNBC) is a highly aggressive breast cancer subtype that lacks effective targeted therapies. Although TNBC is not defined by specific therapeutic targets, a subset of patients have tumors that overexpress cyclins. High cyclin D/E expression catalyzes CDK4/2 activity. In turn, CDK4/2 can non-canonically phosphorylate Smad3, a key TGFβ signaling intermediate, and this phosphorylation has been associated with the shift from tumor-suppressive to oncogenic TGFβ pathway action in breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 56 publications
(99 reference statements)
0
25
0
Order By: Relevance
“…In TNBC, TGF‐β was shown to induce EMT and metastasis . Smad family members such as Smad2, Smad3 and Smad4 mediated these processes . Our in silico analysis showed that CD155 was positively correlated with TGF‐β and Smad3 but not Smad2 and Smad4.…”
Section: Discussionmentioning
confidence: 72%
“…In TNBC, TGF‐β was shown to induce EMT and metastasis . Smad family members such as Smad2, Smad3 and Smad4 mediated these processes . Our in silico analysis showed that CD155 was positively correlated with TGF‐β and Smad3 but not Smad2 and Smad4.…”
Section: Discussionmentioning
confidence: 72%
“…Phosphorylated Thr179-Pro motif of Smad2/3 interacts with Pin1 in a TGF-β-dependent manner, inducing migration and invasion via N-cadherin in prostate cancer cells (Matsuura et al, 2010). In turn, Pin1-Smad3 interaction is reduced by the inhibition of CDK-mediated Smad3 phosphorylation, leading to the suppression of triple negative breast cancer cells (Thomas et al, 2017).…”
Section: Pin1 Activates Invasion and Metastasismentioning
confidence: 99%
“…Pin1 promotes cell proliferation by upregulating cyclins in hepatocellular carcinoma cells 27 . Pin1 also interacts with Smad3 to drive oncogenic TGFβ signalling and promote breast cancer progression 28 . Our RNA sequencing results from the different Pin1‐expressing cell lines provide support for the idea that Pin1 might implement its oncogenic effect by regulating NF‐κB signalling in PDAC.…”
Section: Discussionmentioning
confidence: 56%